Dynamic monitoring of historical masonry structures for damage identification - Ramos, Luís F. (2008)
Two monuments in Portugal are being continually monitoring by University of Minho: the Church of Jerónimos Monastery, in Lisbon, and the Clock Tower of Mogadouro. Vibration sensors and temperature and relative air humidity sensors are installed. Operational modal analysis is being used to estimate the modal parameters and statistical analysis is used to evaluate the environmental effects on the dynamic response. The aim is to explore damage assessment at an early stage by vibration signatures as a part of the heath monitoring process to preserve the historical constructions. The paper presents the dynamic monitoring systems, the automatic operational modal analysis, and the analysis to filter the environmental effects from the dynamic response of the structures. Two subspace based damage detection technique are then applied to detect changes in the modal properties of the structure. The fist method is based on the correlation between the modal parameters and the environmental effects and the second method is based on the computation of a residual to perform detection without reidentification of the modal properties during time. It is shown that the later is robust to temperature and to humidity, and also able to detect small modal variations, like those induced by small earthquake events.